2011
DOI: 10.4048/jbc.2011.14.1.28
|View full text |Cite
|
Sign up to set email alerts
|

Incidental Breast Cancers Identified in the One-Stop Symptomatic Breast Clinic

Abstract: PurposeBreast cancers can be asymptomatic at an early stage and hence screening programmes play an important role in detecting breast cancers early. Even in those patients who present with breast symptoms, breast cancers may be present at a site remote to the site of symptoms. In this study, we aimed to assess the frequency, site and imaging modality used to identify these incidental cancers in the symptomatic one-stop breast clinic.MethodsAll patients who were seen in our breast clinic with breast symptoms ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…there were no clinics that accepted referrals where there was a general suspicion of cancer. The indications for referral included: seven studies on post-menopausal or abnormal vaginal bleeding (20)(21)(22)(23)(24)(25)(26), six studies on breast symptoms (14,15,(27)(28)(29)(30), three for lower gastrointestinal (GI) symptoms (16,31,32), three for elevated prostate specific antigen (PSA) (17,18,33), three for testicular symptoms (34)(35)(36), two for urological symptoms (37,38), two for dyspepsia (39,40), one for haematuria (19), one for unexplained lymphadenopathy (41), and one for neck lumps (6). When reported, one-stop clinics were held in a hospital setting.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…there were no clinics that accepted referrals where there was a general suspicion of cancer. The indications for referral included: seven studies on post-menopausal or abnormal vaginal bleeding (20)(21)(22)(23)(24)(25)(26), six studies on breast symptoms (14,15,(27)(28)(29)(30), three for lower gastrointestinal (GI) symptoms (16,31,32), three for elevated prostate specific antigen (PSA) (17,18,33), three for testicular symptoms (34)(35)(36), two for urological symptoms (37,38), two for dyspepsia (39,40), one for haematuria (19), one for unexplained lymphadenopathy (41), and one for neck lumps (6). When reported, one-stop clinics were held in a hospital setting.…”
Section: Resultsmentioning
confidence: 99%
“…Overdiagnosis of cancer is most commonly described in the context of screening but it is possible to diagnose cancer in patients with symptoms from another cause, especially when lower risk patients are tested (50). Based on the findings of this review, we are unable to comment on the risk of overdiagnosis in one-stop clinics: only one study reported patients diagnosed with asymptomatic breast cancer and most also had symptomatic breast cancer (29). Some authors considered the CR's for cancer and serious disease to be too low (30,39) whilst others concluded that testing more patients to reduce the risk of under-diagnosis was important (19,37).…”
Section: Implications For Research and Practicementioning
confidence: 85%
See 1 more Smart Citation
“…While the majority of known cases present with symptomatic breast lumps, a minority may remain asymptomatic, with the tumor being incidentally detected during routine imaging or self-examination. In some instances, patients initially diagnosed with benign breast masses may later seek secondary opinions due to persistent symptoms or suspicion of misdiagnosis, as observed in our patient, possibly attributed to sampling errors or misinterpretation of imaging findings [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study published in the Journal of Breast Cancer , Mehrotra et al [ 1 ] reported incidental breast cancers identified in a one-stop symptomatic breast clinic where patients receive the results of their radiological examinations and tissue sampling on the same day. Medical environments differ from country to country and from culture to culture.…”
mentioning
confidence: 99%